1995
DOI: 10.1007/bf02079065
|View full text |Cite
|
Sign up to set email alerts
|

Final height and predicted height in boys with untreated constitutional growth delay

Abstract: We report on 49 boys with constitutional growth delay (CGD) who were initially seen in our clinic at a mean chronological age of 13.3 years (range, 7.3-16.4) and a bone age of 11.1 years (range, 6.0-13.5). All were below the 5th height percentile for chronological age. A positive family history with delayed growth and puberty in one or both parents could be elicited in 75%. All 49 patients were re-examined at a mean age of 22.9 years (range, 20.4-31.2). Measured final height was 171.3 cm (range, 161.2-181.7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
33
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 28 publications
11
33
2
Order By: Relevance
“…However, not all boys with CDGP reach their genetic TH [7, 9, 10, 13]. Although in some previous studies FH of CDGP cases was only 0.1–0.2 SDs smaller than their TH [5, 8], several other studies have reported FH from 0.8 to 1.5 SDs below TH [7, 8,10,11,12,13].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, not all boys with CDGP reach their genetic TH [7, 9, 10, 13]. Although in some previous studies FH of CDGP cases was only 0.1–0.2 SDs smaller than their TH [5, 8], several other studies have reported FH from 0.8 to 1.5 SDs below TH [7, 8,10,11,12,13].…”
Section: Discussionmentioning
confidence: 96%
“…Subjects with CDGP have previously been shown to achieve FH that is normal or lower-range normal compared with the general population, with values ranging from –1.9 to –0.6 SDs [5,6,7,8,9,10, 12]. However, not all boys with CDGP reach their genetic TH [7, 9, 10, 13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is still no consensus on the issue whether boys with a delayed puberty reach a final height appropriate for their target height [1, 2,7,8,9,10,11,12,13]. Most authors found that boys with pubertal delay reach a final height appropriate for their parental centiles, while others claim final height was significantly below target height [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%